The gender issue: epidemiology of ankle injuries in athletes who participate in basketball - Hosea, T. M.; Carey, C. C.; Harrer, M. F. (Clinical Orthopaedics and Related Research, 2000)
The increased participation of women in organized athletics has resulted in an interest in gender-related injury patterns. Previous reports have indicated an increased incidence in anterior cruciate knee injuries among female intercollegiate basketball players compared with their male counterparts. The current epidemiologic study prospectively evaluated the relative risk of ankle injuries in scholastic and collegiate basketball players during a 2-year period. Eleven thousand seven hundred eighty athletes participated in this study, 4940 females and 6840 males. There were 1052 ankle injuries. Overall, females had a 25% greater risk of sustaining a Grade ankle sprain compared with their male counterparts. This increased risk was present in the interscholastic and intercollegiate players. There was no significant difference in the risk for Grades II and III ankle sprains, ankle fractures, or syndesmotic sprains. Male and female athletes doubled their risk for sustaining an ankle injury at the intercollegiate level compared with the interscholastic level.